Oncogenic signaling in the Drosophila prostate-like accessory gland activates a pro-tumorigenic program in the absence of proliferation. - Church, S.J.; Pulianmackal, A.J.; Dixon, J.A.; Loftus, L.V.; Amend, S.R.; Pienta, K.; Cackowski, F.C.; Buttitta, L.A. (Disease models & mechanisms, 2025)
Drosophila models for tumorigenesis have revealed conserved mechanisms of signaling involved in mammalian cancer. Many of these models use highly mitotically active Drosophila tissues. Few Drosophila tumorigenesis models use adult tissues, when most cells are terminally differentiated and postmitotic. The Drosophila accessory glands are prostate-like tissues, and a model for prostate tumorigenesis using this tissue has been explored. In this prior model, oncogenic signaling was induced during the proliferative stages of accessory gland development, raising the question of how oncogenic activity impacts the terminally differentiated, postmitotic adult tissue. Here, we show that oncogenic signaling in the adult Drosophila accessory gland leads to activation of a conserved pro-tumorigenic program, similar to that of mitotic tissues, but in the absence of proliferation. In our experiments, oncogenic signaling in the adult gland led to tissue hypertrophy with nuclear anaplasia, in part through endoreduplication. Oncogene-induced gene expression changes in the adult Drosophila prostate-like model overlapped with those in polyploid prostate cancer cells after chemotherapy, which potentially mediate tumor recurrence. Thus, the adult accessory glands provide a useful model for aspects of prostate cancer progression that lack cellular proliferation.